Reconsidering Toronto's Emergence as a Metropolis: Some Evidence from the Census - Sentance, Jim (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1984)
The metropolitan thesis of N.S.B. Gras has been used in examining the development of several of Canada's foremost cities, and its use in a more general approach to Canadian urban history has been persuasively argued by J.M.S. Careless. This paper, while accepting the usefulness of the model, finds simplistic interpretations of Gras and anecdotal evidentiary standards to have marred much of the applied work. An effort is made to state more clearly the meaning of the process of stages described by Gras, and to test the timing of the metropolitan emergence of the city of Toronto using this understanding and employment data from the Census.